In Vitro and Ex Vivo Selection Procedures for Identifying Potentially Therapeutic DNA and RNA Molecules - Soledad Marton; José A. Reyes-Darias; Francisco J. Sánchez-Luque; Cristina Romero-López; Alfredo Berzal-Herranz (Molecules, 2010)
It was only relatively recently discovered that nucleic acids participate in a variety of biological functions, besides the storage and transmission of genetic information. Quite apart from the nucleotide sequence, it is now clear that the structure of a nucleic acid plays an essential role in its functionality, enabling catalysis and specific binding reactions. In vitro selection and evolution strategies have been extremely useful in the analysis of functional RNA and DNA molecules, helping to expand our knowledge of their functional repertoire and to identify and optimize DNA and RNA molecules with potential therapeutic and diagnostic applications. The great progress made in this field has prompted the development of ex vivo methods for selecting functional nucleic acids in the cellular environment. This review summarizes the most important and most recent applications of in vitro and ex vivo selection strategies aimed at exploring the therapeutic potential of nucleic acids.